A melhoria da atuação do fiscal de contrato por intermédio de uma proposta de desenvolvimento e uso de um aplicativo - Almeida, Aldrei Duarte de (2023)
The supervision of administrative contracts is a sensitive task to be carried out by public agents and, when it is not done effectively, it generates damage to the public machine and the consequent accountability of those involved, especially the designated contract inspectors. Thus, it is necessary to implement mechanisms that can improve the supervision of administrative contracts. The problem of this research is: "How can the supervision of administrative contracts be improved by means of a technological tool, so as to allow for greater control and effectiveness in public contracting?". Thus, the general objective of this research was to develop a proposal for an application for monitoring administrative contracts in order to improve the performance of the contract inspector in the Public Administration. The theoretical framework covered subjects related to e-government, the adoption of Information and Communication Technologies (ICTs) as an e-government tool, public procurement, bidding, administrative contracts and the adoption of technologies in public procurement. The study is characterized as applied research, with a qualitative approach and a descriptive nature. As for the form of investigation used, a case study was adopted, which was carried out at the Brazilian Army's School for the Improvement of Weapons Sergeants (EASA). A bibliographic and documentary survey was carried out, as well as in-depth interviews in order to collect data that could contribute to the development of a proposal for an application for monitoring administrative contracts. To this end, a total of eleven contract inspectors were interviewed at EASA, working on service contracts under the common indirect execution system. Using content analysis, an interpretation was made according to the parameters indicated by the laws, documents and authors, making the appropriate comparisons according to the problem and the proposed objectives, extracting from the interviews the attributes needed to make up the proposal for an application. The result was a proposal for an application that was simple to develop, free of charge and whose content was drawn up in accordance with legislation, scientific production on contract monitoring, ICTs and also based on the experiences of current contract inspectors. Thus, it has become possible, through this application, to inspect contracts, archive inspections already carried out by the user, consult specific legislation on the subject, have access to step-by-step mementos for inspecting certain contracts, access and make checklists and reports, as well as consult frequently asked questions, all of which contributes to improving the performance of contract inspectors in the Public Administration.